Karakteristik pasien gout arthritis di Rumah Sakit Umum Pusat Sanglah Denpasar periode 2014-2015 - Rhama, Bagus; Kambayana, Gede (E-Jurnal Medika Udayana; Vol 7 No 2 (2018): E-Jurnal Medika Udayana, 2018)
Gout Arthritis is defined as one of a metabolic disorder called hyperuricaemia, where at any given moment to be blood consist some uric acid in the high levels. Associated with the presence of monosodium urate in leukocytes, usually found in the synovial joint fluid, monosodium urate crystals in the tissues (tophus), interstitial renal disease, gout and nephrolithiasis. Using a cross sectional design of Study for Gout Arthritis patients at General Hospital Sanglah period 2014-2015 which aims to find out the number of patient characteristics are gender, age, level of uric acid (hyperuricaemia Status), and the status of tophus. Gout Arthritis is obtained in 20 patients who were in Sanglah General Hospital, Denpasar. Of the 20 patients, the study sample obtained a total of 11 samples, 9 patients including exclusion criteria. Obtained a mean age of 57.18 + 2:27 years. Gout Arthritis patients male sex more that 10 (90.9%) than women 1 (9.1%). Comparison men: women is 10: 1. Age samples were in the range 42-65 years figures. A total of 4 samples (36.36%) stage Chronic Gout Arthritis and 7 other samples (63.63%) stage of Acute Gout Arthritis. Keywords: tophus, gout, metatarsalpalangeal